Impact of Macroeconomic Policieson Income Distribution : An Empirical Study. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
There has been a growing awareness of the income distribution dimension of macroeconomic policies. This paper presents a framework for studying this issue empirically, and considers the case of the Philippines using data available from integrated surveys of households. After developing and estimating an analytical model, it was found that underemployment, inflation, and government spending worsen income distribution, while productivity gains, the real interest rate, and the real exchange rate were found to be progressive instruments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet